Insight on Some Interesting Models of Parallel Universe - Rimo Sarkar (Faculty of Science and Education, UIN Walisongo Semarang, 2022)
The theoretical perspective on universe is the most intriguing subject of discussion. Human's curiosity made them wandered about the origin and form of the universe and because of the attempt to find those answers the idea of the parallel universe came into the light. This study has been undertaken to investigate and gain insight about some models of parallel universes. We have described models that are most fascinating. The inquiry isn't if the multiverse really exists or not but if they exists how are they like and where they might be.